Qashash Al-Qur'an as Hypnoparenting in Children in Neuroscience Perspective - Risky, Abu; Suyadi; Husain, Andi Musthafa (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2023)
The stories within the Qashash al-Qur'an are incredibly captivating and leave a profound impression on those who contemplate them. Stories that carry profound wisdom have a remarkable ability to capture attention and stimulate the mind. Children enjoy listening to these stories as they embrace the values of Islamic education without feeling coerced. Examples include the stories of the prophets and narratives of past individuals, from which wisdom and lessons can be extracted from their life journeys. Employing a qualitative descriptive approach, this article seeks to explore this phenomenon. It argues that in order to instill these important values within the souls of young children, an effective educational method is through the study of hypnoparenting from a neuropsychological perspective. As children prepare for sleep, their brain waves transition from beta to alpha, allowing information and messages conveyed during this time to be stored in their subconscious. The data and information embedded within the subconscious mind will subsequently influence the child's thoughts, behaviors, and emotions in the future.